Proteome profiling of vascular sap regarding Eucalyptus grandis, Eucalyptus urophylla, and Eucalyptus camaldulensis - da Silva, Felipe Alexsander Rodrigues [UNESP]; Balbuena, Tiago Santana [UNESP] (Wiley, 2023)
The plant vascular system is a key element for long-distance communication. Understanding its composition may provide valuable information on how plants grow and develop themselves. In this study, a quantitative proteome dataset of the vascular sap proteome of three commercially important Eucalyptus species was shown. Protein extraction was carried out using a pressure bomb, whereas only in silico predicted extracellular proteins were considered as part of the sap proteome. A total of 132 different proteins were identified in all three Eucalyptus species and the most abundant proteome subset within all three species was comprised of proteins involved in the carbohydrate metabolic process, proteolysis, components of membrane, and defense response. The sap proteome of the species E. grandis and E. urophylla revealed the highest similarities. Functional classification indicated that the sap proteome of E. grandis and E. urophylla are mostly comprised of proteins involved in defense response and proteolysis; whereas no prominent functional class was observed for the E. camaldulensis species. Quantitative comparison highlighted characteristic sap proteins in each of the Eucalyptus species. The results that could be found in this study can be used as a reference for the proteome sap analysis of Eucalyptus plants grown under different conditions.
Keywords: innate immunity; long-distance signaling; plant proteomics